Prunus gyirongensis, a new name for Padus integrifolia (Rosaceae) - Tong, Yihua; Xia, Nianhe (Phytotaxa, 2017)
Prunus Linnaeus (1753: 473) s.l. consists of approximately 250 species distributed across the Northern Hemisphere and into the subtropics and tropics (Wen et al. 2008). In the long taxonomic history of this genus, there are two main opinions: some botanists inclined to split Prunus s.l. into multiple genera (Yu et al. 1986, Takhtajan 1997, Lu et al. 2003), while the others maintained the genus Prunus s.l. and recognized groups at sectional or subgenera levels (Chin et al. 2010, Shi et al. 2013, Eisenman 2015).